Pengaruh Program Pelatihan K3 Terhadap Pengurangan Kecelakaan Kerja di Sektor Konstruksi - Alelga, Elsa; Susilawati, Susilawati (PT. Alahyan Publisher Sukabumi, 2025)
Occupational Safety and Health (OSH) training programs in the construction sector have been shown to have a significant impact in reducing work accidents. Through a desk study approach with qualitative methods, this research reveals that OHS training not only increases workers’ awareness and knowledge of safety practices but also results in a meaningful decrease in the number of workplace accidents. In addition, the OHS training also succeeded in changing behavior and establishing a stronger safety culture in the workplace, where workers became more proactive in reporting hazardous conditions and more disciplined in complying with safety procedures. Project management also experiences direct benefits from OHS training, with higher compliance with occupational safety and health standards, which improves project efficiency and productivity. Emphasis on a holistic and sustainable OHS training approach is therefore key to ensuring the safety and health of workers and the future success of construction projects.